International Role Perspective of Indonesia’s Participation in the Second United Nations Emergency Force (UNEF II) 1975–1977 - Safi, Fathomi Abdillah; Kurniawan, Yandry (The Republic of Indonesia Defense University, 2024)
This article analyzes Indonesia's envisioned international role as it maintained its deployment of armed forces as part of the Garuda Contingent in the Second United Nations Emergency Forces (UNEF II) mission from 1975 to 1977, despite concurrently conducting military operations in Portuguese Timor. This research uses role theory as an analytical framework to explain Indonesia's objectives and role in deploying peacekeepers abroad during the greatest military deployment since independence. By applying a qualitative-deductive approach, the final results of this article indicate that Indonesia has sent the Garuda VIII Contingents to UNEF II as part of Indonesia's commitment to world peace and supporting the principles of the United Nations. In addition, Indonesia is striving to strengthen its diplomatic position and gain legitimacy from international states. Despite the conflict in Portuguese Timor, Indonesia remains consistent in fulfilling its role and responsibilities as a state of international peace and security. This research provides a better understanding of the motivation and role that Indonesia wants to take on one of its peacekeeping missions and its contribution to regional and global stability.